Strategies for Editing Virulent Staphylococcal Phages Using CRISPR-Cas10 - Nayeemul Bari, S. M. (ACS Synth Biol, 2017)
Staphylococci are prevalent skin-dwelling bacteria that are also leading causes of antibiotic-resistant infections. Viruses that infect and lyse these organisms (virulent staphylococcal phages) can be used as alternatives to conventional antibiotics and represent promising tools to eliminate or manipulate specific species in the microbiome. However, since over half their genes have unknown functions, virulent staphylococcal phages carry inherent risk to cause unknown downstream side effects. Further, their swift and destructive reproductive cycle make them intractable by current genetic engineering techniques. CRISPR-Cas10 is an elaborate prokaryotic immune system that employs small RNAs and a multisubunit protein complex to detect and destroy phages and other foreign nucleic acids. Some staphylococci naturally possess CRISPR-Cas10 systems, thus providing an attractive tool already installed in the host chromosome to harness for phage genome engineering. However, the efficiency of CRISPR-Cas10 immunity against virulent staphylococcal phages and corresponding utility as a tool to facilitate their genome editing has not been explored. Here, we show that the CRISPR-Cas10 system native to Staphylococcus epidermidis exhibits robust immunity against diverse virulent staphylococcal phages. On the basis of this activity, a general two-step approach was developed to edit these phages that relies upon homologous recombination machinery encoded in the host. Variations of this approach to edit toxic phage genes and access phages that infect CRISPR-less staphylococci are also presented. This versatile set of genetic tools enables the systematic study of phage genes of unknown functions and the design of genetically defined phage-based antimicrobials that can eliminate or manipulate specific Staphylococcus species.